Ligas beta Ti-Nb-Zr(-Ta-Mo) multiprincipais com baixo módulo de elasticidade - Santos, Rafael Formenton Macedo dos (2023)
The use of Ti-6Al-4V alloy as a biomaterial is more convenient among Ti alloys, as it is produced on a larger scale due to aeronautical applications. However, it is known that Ti-6Al-4V alloy can be harmful to the patient’s health (due to the toxicity of Al and V) and it does not have the most adequate properties. Biomaterials’ scientific and technological development becomes necessary, especially those with application in orthopedics, once there is an increase in life expectancy. The metallic alloys currently used in Brazil have a modulus of elasticity (E) much higher than that of human bone (E = 10 to 30 GPa), such as steel (200 GPa), Co-Cr Alloys (220 GPa), Ti -6Al-4V (110 GPa) and, therefore, the search for alloys with better mechanical and chemical biocompatibility is necessary. The β-Ti (CCC) alloys show good mechanical (elasticity modulus, E = 44 to 80 GPa) and chemical (good corrosion resistance) biocompatibility. At present, the development of multicomponent, equimass, stable β-Ti alloys with medium and high entropy of the systems Ti-33Nb-33Zr, Ti-25Nb-25Zr-25Ta, Ti- 20Nb-20Zr-20Ta-20Mo (% weight ), in addition to alloys from the Ti-40Nb-xZr system with high Zr fractions and based on electronic parameters Bo and Md seeking an optimal value of modulus of elasticity (between 40 and 60 GPa). For the Ti-Nb-Zr ternary system, the new βTAP ratio (ternary alloy parameter) was determined and the higher its value, the lower the alloy’s modulus of elasticity. The Ti-40Nb-40Zr alloy showed the lowest modulus of elasticity (E = 42 GPa) in the rolled condition. The Ti-25Nb-25Zr-25Ta alloy showed better results in biological tests (adhesion and cell viability assay), and better combination of low modulus (E = 70 GPa) and high mechanical strength, making it possible to reconcile these properties in β multicomponent.